Association between poverty indicators and social relations. (1st October 2020) - Albert, Fruzsina; Hajdu, Gábor
Abstract : We analyse the association between poverty indicators and social relations using nationally representative data from Hungary. We focus on four poverty indicators (the three standard indicators of Eurostat and perceived financial problems) and a rich set of social relationship indicators (18 variables). Material deprivation is the most strongly linked to the measures of social ties and social integration, whereas income poverty is associated the least strongly with them. Although income poverty is probably the most widely used poverty indicator, our results suggest that material deprivation and even subjective poverty reflect better the multidimensional nature of poverty and social exclusion.